2022
DOI: 10.1002/cncr.34370
|View full text |Cite
|
Sign up to set email alerts
|

Clinical activity of checkpoint inhibitors in angiosarcoma: A retrospective cohort study

Abstract: Background Systemic treatments for angiosarcoma remains an area of unmet clinical need. The authors conducted this retrospective study to assess the clinical activity of checkpoint inhibitors in patients with angiosarcoma. The primary objective was to assess the objective response rate, and the secondary objective was to assess the progression‐free and overall survival durations and disease control rate. Methods Patient data were obtained using The University of Texas MD Anderson Cancer Center Tumor Registry d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Pembrolizumab showed a durable clinical response with mPFS of 6.2 months and OS of 72.6 months. 27 Future prospective studies evaluating targeted therapies and immunotherapy in cardiac angiosarcoma would be valuable, even though the rarity of the disease limits the scope of conducting large-scale studies.…”
Section: Discussionmentioning
confidence: 99%
“…Pembrolizumab showed a durable clinical response with mPFS of 6.2 months and OS of 72.6 months. 27 Future prospective studies evaluating targeted therapies and immunotherapy in cardiac angiosarcoma would be valuable, even though the rarity of the disease limits the scope of conducting large-scale studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, targeted anti-angiogenic drugs and immune checkpoint inhibitors(ICIs) have been applied in clinical practice and achieved good results [ 10 12 ].Especially in angiosarcoma, data on the efficacy of immunotherapy are few but consistent in demonstrating excellent antitumour activity. A retrospective study found that patients with visceral angiosarcoma, including cardiac angiosarcoma, treated with pembrolizumab as monotherapy can also obtain progression-free survival (PFS) similar to other systemic treatments [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In view of an approach to increasingly personalized medicine, the characterization of the immune landscape of a tumor becomes an important factor in the identification and stratification of patients who are likely to benefit from immunotherapy-based treatment strategies. This is particularly important for HSA which, even in human medicine, has limited therapeutic possibilities and a poor prognosis and in which emerging data suggest that alternative approaches with the use of immune checkpoint inhibitors are effective [86]. Con-tradicting results emerged from a retrospective study comparing the clinical characteristics and the results of targeted exome sequencing, transcriptome sequencing, and immunohistochemistry analyses in human patients with histologically confirmed angiosarcoma treated with immune checkpoint blockade-base therapy, where it was demonstrated that neither PD-L1 expression nor presence of TILs at baseline appears necessary for a response to immune checkpoint blockade (ICB) therapy [86].…”
Section: Discussionmentioning
confidence: 99%